PENGARUH KEPERCAYAAN, KEMUDAHAN DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN JASA GOJEK DI KOTA SEMARANG YANG DIMEDIASI MINAT BELI SEBAGAI VARIABEL INTERVENING - Arif Reza Maharama; Noor Kholis (Jurnal Ekonomi dan Bisnis, 2018)
Trust, Ease, Risk Perception and Buying Interest Consumers are one of the factors that areexpected to improve Buying Service Decision Go-Jek online transportation in Semarang City.The formulation of the problem in this research is to know how the influence of trust, easeand perception of risk to purchasing decision of Go-Jek service in Semarang City, throughconsumer buying interest as intervening variable. The purpose of this study was to analyze theinfluence of trust, convenience, and risk perception of purchasing decision through consumerbuying interest as intervening variable. The population in this study is the consumer of Go-Jektransportation users in Semarang City with a sample of 120 people using the formula RaoPurba. Methods of collecting documentation data and questionnaires, analytical methodsof instrument test (validity test and reliability test), descriptive analysis of index answers pervariable, classical assumption test and regresion path analysis, and using the test of sobel.The result of the research shows that there is positive and significant influence of trust, ease ofbuying decision of service with consumer buying interest as intervening variable, and there isnegative and significant influence of risk perception to purchase decision with buying interestas intervening variable. The buying interest variable able to mediate the influence of trust, easeand perception of risk to purchase decision is evidenced by the test of sobel.Keywords : Trust, Ease, Risk Perception, Buying Interest, Buying DecisionTrust, Ease, Risk Perception and Buying Interest Consumers are one of the factors that areexpected to improve Buying Service Decision Go-Jek online transportation in Semarang City.The formulation of the problem in this research is to know how the influence of trust, easeand perception of risk to purchasing decision of Go-Jek service in Semarang City, throughconsumer buying interest as intervening variable. The purpose of this study was to analyze theinfluence of trust, convenience, and risk perception of purchasing decision through consumerbuying interest as intervening variable. The population in this study is the consumer of Go-Jektransportation users in Semarang City with a sample of 120 people using the formula RaoPurba. Methods of collecting documentation data and questionnaires, analytical methodsof instrument test (validity test and reliability test), descriptive analysis of index answers pervariable, classical assumption test and regresion path analysis, and using the test of sobel.The result of the research shows that there is positive and significant influence of trust, ease ofbuying decision of service with consumer buying interest as intervening variable, and there isnegative and significant influence of risk perception to purchase decision with buying interestas intervening variable. The buying interest variable able to mediate the influence of trust, easeand perception of risk to purchase decision is evidenced by the test of sobel.Keywords : Trust, Ease, Risk Perception, Buying Interest, Buying Decision